An Open Slot Antenna with Bandwidth Extension for WLAN/UWB Applications. (18th February 2015) - Deng, Jing-Ya; Fan, Tian-Qi; Zhang, Yan; Wen, Xiang; Liu, Guo-Qiang; Guo, Li-Xin
Abstract : An open slot antenna with extended bandwidth for WLAN and UWB applications is proposed. The radiating structure is composed of a rectangular microstrip patch antenna exciting an L-shaped slot etched on the ground plane. The feed position is optimized to get better impedance match for the higher range of the UWB spectrum, while a step in the slot, realized in the ground plane, is employed to extend the lower limit of the bandwidth so as to cover the 2.4 GHz WLAN frequency band. Using these design solutions the antenna bandwidth is successfully extended to 140% so as to cover both the WLAN and the UWB spectrum.